2016
DOI: 10.17645/mac.v4i3.522
|View full text |Cite
|
Sign up to set email alerts
|

Marketing to Youth in the Digital Age: The Promotion of Unhealthy Products and Health Promoting Behaviours on Social Media

Abstract: The near-ubiquitous use of social media among adolescents and young adults creates opportunities for both corporate brands and health promotion agencies to target and engage with young audiences in unprecedented ways. Traditional media is known to have both a positive and negative influence on youth health behaviours, but the impact of social media is less well understood. This paper first summarises current evidence around adolescents' exposure to the promotion and marketing of unhealthy products such as ener… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
61
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(73 citation statements)
references
References 64 publications
(77 reference statements)
2
61
0
3
Order By: Relevance
“…This study contributes to the literature on food, beverage, and snack marketing in several ways. Other social media research studies have included a smaller subset of brands, fewer social media platforms, or provided a narrative review of evidence or broad commentaries on public health concerns related to social media advertising . Our findings are the first to evaluate growth of brands' social media accounts over a 9‐year period and capture the variety of advertising practices companies used on five platforms over a 1‐year period of time.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This study contributes to the literature on food, beverage, and snack marketing in several ways. Other social media research studies have included a smaller subset of brands, fewer social media platforms, or provided a narrative review of evidence or broad commentaries on public health concerns related to social media advertising . Our findings are the first to evaluate growth of brands' social media accounts over a 9‐year period and capture the variety of advertising practices companies used on five platforms over a 1‐year period of time.…”
Section: Discussionmentioning
confidence: 99%
“…Other social media research studies have included a smaller subset of brands, 23,26,36 fewer social media platforms, 26,36 or provided a narrative review of evidence or broad commentaries on public health concerns related to social media advertising. 23,25,27,28 Our findings are the first to evaluate growth of brands' social media accounts over a 9-year period and capture the variety of advertising practices companies used on five platforms over a 1-year period of time. Our data, therefore, present the most comprehensive snapshot of social media food advertising to date and can provide a roadmap for future studies aiming to examine the effects of novel promotional techniques that are unique to social media food advertising (eg, using interactive features in posts that depict adolescents).…”
Section: Discussionmentioning
confidence: 99%
“…They do so by gathering viewers' ideas, which "might be better than the ones they (the brand/influencer) had", so that the brand can create better future campaigns. Indeed, advertisements that are targeted, such as those tailored to viewers' preferences, are found to be particularly impactful [81,82]. In addition, many recognised that viewers would need to purchase Nutella in order to share these images and recipe ideas and so sales of Nutella would increase.…”
Section: Theme 2: the Accessibility Of Youtubers Increases Children'smentioning
confidence: 99%
“…[31] Emerging evidence shows that exposure to marketing of the unhealthy products through social media platforms may impact adolescent health behaviors. [32] Given that 92% U.S. adolescents report going online daily, with 71% using Facebook,[33] the current study expands on previously identified correlates by examining social media engagement and exposure to online tobacco advertising and their associations with hookah use in a representative sample of high school students in North Carolina. We also examined associations between hookah use and youth exposure to anti-tobacco messages, along with school and community tobacco prevention activities.…”
Section: Introductionmentioning
confidence: 99%